Men and Women in Science: Differences on the Example of Solo Research - Kwiek, Marek (Sensus Historiae, 2022)
Single-authored publications continue to play a key role in unambiguously signaling research capabilities of scientists and scholars, especially in social sciences and humanities. The effects of the choices of publication strategies - the choice of authorship type, journal type, and especially its reach, language and prestige - influence the shape of an individual academic career over decades of functioning in science. The cumulative effect of advantages (and successes) is at work here, representing the opposite of the cumulative effect of disadvantages (and failures) over time, leading to differential access to academic recognition on the one hand, and to scientific promotions and research grants on the other. Men and women in science function according to the same rules, but the list of inequalities presented is certainly not shrinking today. Solo research is especially important to be kept in mind at the early stages of an academic career, when, at least in theory, all opportunities are still open according to the meritocratic postulate of the functioning of the science system.